Cultural Heritage Digitalization on Traditional Sundanese Music Instrument Using Augmented Reality Markerless Marker Method - Budi Arifitama; Ade Syahputra (Jurnal Teknologi dan Sistem Komputer, 2017)
Research into cultural heritage which implements augmented reality technology is limited. Most recent research on cultural heritage are limited on storing data and information in the form of databases, this creates a disadvantage for people who wants to see and feel at the same moment on actual cultural heritage objects. This paper, proposes a solution which could merge the existing cultural object with people using augmented reality technology. This technology would preserve traditional instrument in the form of 3D object which can be digitally protected. The result showed that the use of augmented reality on preserving cultural heritage would benefit people who try to protect their culture.